Screw-press gluing in timber construction – press force predictions and application limits - Simon Aicher; Aaron Münzer; Kai Simon (Results in Engineering)
Screw-press gluing is a highly efficient and often the exclusive possibility to join components of ribbed wooden elements and for plate or strip type reinforcement of timber structures. This paper deals with the magnitude of the press force exerted by the head of partially threaded screws then balanced by the screw’s withdrawal and torque capacity which is decisive for the clamping pressure. The investigations comprised screw diameters of 5 to 10 mm with countersunk and flange-type head diameters up to 30 mm. Four sheathing materials were included: Spruce solid timber, cross-layered laminated veneer lumber from spruce and hardwood plywood made of birch and beech wood. The base material was throughout glued-laminated timber from spruce. The screw force was determined by two methods being (i) head pull-through tests, coarsely aligned with EN 1383, and (ii) drill-in experiments with simultaneous measurement of applied torque, press force and screw head indentation. A good agreement of both test methods with regard to press force was obtained and described by multi-variable regressions. For practical application simple press force predictions based on screw head diameter were derived relying on mean values rather than 5 %-quantiles stipulated too conservative in the European timber structures execution standard FprEN1995–3. Screw-press gluing of hardwood sheathings with flange head fasteners should be excluded from application due to observed predominant screw torque ruptures or spinning loose failures. These features are attributed to exceedance of the torsional resistance or withdrawal capacity of the screw already within the very first millimeters of indentation.